Pengembangan Model Konseptual Niat Pembayaran Pajak Pelaku E-Commerce - Sari Dewi (Owner : Riset dan Jurnal Akuntansi, 2021)
Ecommerce transactions are one of the complex and growing types of transactions in Indonesia. Ecommerce trade is currently experiencing very rapid progress which is marked by a growing improvement in current technological advances, especially in the field of e-commerce. The largest state revenue can be seen from the 2019 State Revenue and Expenditure Budget of state revenues of 1,786.4 trillion rupiahs from taxes. The Ministry of Finance enforces the Minister of Finance Regulation Number 210/PMK.010/2018 concerning Tax Treatment of Trading Transactions Through Electronic Systems. In response to this, there is the potential for an exodus of e-commerce players to switch to using social media as a place for online buying and selling transactions. The payment intention factor for e-commerce transactions is based on three aspects, namely, knowledge and understanding of taxation. Internal influences in the form of taxpayer awareness, ethics, the use of information technology which is influenced by the external readiness of information technology, as well as the influence of the taxpayer's environment. This study aims to propose a conceptual model to identify the factors that influence the tax payment intention of e-commerce actors. This research is expected to provide suggestions to the Directorate General of Taxes regarding e-commerce taxpayers.